2019
DOI: 10.1111/bcpt.13292
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam concentration in hair is associated with the time schedule of administration: Study on rats

Abstract: Measurement of hair drug content may be a reliable biomarker of the history of drug exposure, allowing to assess patient long‐term compliance. Studies on correlations between antiepileptic drugs intake and their hair contents are limited. The aim of the study was to determine the association between the history of levetiracetam administration and its content in rat hair in controlled laboratory conditions. Additionally, the effects of levetiracetam on hair growth rate and body‐weights were examined. Three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Our previous published rat study showed that the levetiracetam accumulation in pulverized hair was correlated with the total number of doses received ( r = .699, P < .001) 10 . We concluded that levetiracetam measured in rat hair represents a reliable marker and may reflect adherence to levetiracetam treatment 10 .…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Our previous published rat study showed that the levetiracetam accumulation in pulverized hair was correlated with the total number of doses received ( r = .699, P < .001) 10 . We concluded that levetiracetam measured in rat hair represents a reliable marker and may reflect adherence to levetiracetam treatment 10 .…”
Section: Introductionmentioning
confidence: 70%
“…10 We concluded that levetiracetam measured in rat hair represents a reliable marker and may reflect adherence to levetiracetam treatment. 10 This time, we conducted a similar study in rats (under the same conditions), but with the aim of comparing the methods of hair sample preparation (cutting vs pulverization) for the analysis of the concentration of the anti-epileptic drug levetiracetam. Choosing the most appropriate method is very important because we wanted to introduce the analysis of levetiracetam concentration in pulverized hair into routine diagnostics in patients with drug-resistant epilepsy.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…All the rats were housed in the same environmental conditions and handled by the same experimenters for at least 30 days before blood sampling. The environmental conditions were as previously described in the study of Zakrzewska et al (2020) . Specifically, the rats were housed in standard plastic cages, in groups of three, with wood chip bedding on the floor, in fully controlled environmental conditions : temperature 22 ± 2 °C, humidity 50% ±5, and 12-hour light/12-hour dark cycles with lights on at 8.00 a.m. All the rats had unlimited access to tap water and standard laboratory chow (Labofeed H, WPIK, Kcynia, Poland) throughout the duration of the study.…”
Section: Methodsmentioning
confidence: 99%